Product-level inherent circularity and its relationship to environmental impact. (1st July 2020) - Linder, Marcus; Boyer, Robert H.W.; Dahllöf, Lisbeth; Vanacore, Emanuela; Hunka, Agnieszka
Abstract: Circular Economy scholarship has developed multiple metrics for assessing product-level circularity. To date, however, many product-level indicators either conflate circularity and environmental impact, or have been validated using a very limited sample of products. This study applies a single metric, "C", to a sample of 18 products in the Swedish marketplace, and compares their C-scores with scores for lifecycle assessment (LCA). LCA scores for sample products are normalized by LCA scores of very similar reference products, allowing for comparison of LCAs across different product varieties. A test for correlation between products' C-scores and LCA ratios reveals a strong, significant, and inverse association between levels of circularity and products' relative environmental impact. The results offer evidence that products whose economic value is composed of relatively more recirculated material have a relatively low impact on the environment. Future research will benefit from applying similar tests to a broader variety of products and developing tools to expedite the accurate measurement of circularity and lifecycle impacts. Highlights: Tests the validity of a product-level metric for inherent circularity (C). Applied to 18 products, with 14 complete calculations of C. Inverse correlation between C and LCAs: GWP100 (−0.84), ADP(-0.88), EPS(-0.89). Evidence that more circular products have lower environmental impact.